The genus Goera Stephens (Trichoptera: Goeridae) in Japan - Nozaki, Takao; Tanida, Kazumi (Zootaxa, 2006)
We revise the Japanese species of Goera (Trichoptera: Goeridae), and confirm 15 species. Six new species, G. akagiae Tanida and Nozaki, G. dilatata Nozaki and Tanida, G. nigrosoma Nozaki and Tanida, G. shikokuensis Nozaki and Tanida, G. tajimaensis Tanida and Nozaki, and G. uchina Tanida and Nozaki, are described. Goera gyotokui Kobayashi and G. nipponensis Navás are synonymized with G. curvispina and G. japonica, respectively. Goera tenuis Ulmer and G. tungusensis Martynov are newly recorded for the Japanese fauna. Females of G. curvispina, G. kawamotonis, G. lepidoptera Schmid, G. spicata Schmid and G. tenuis are described for the first time